"If I wasn’t a pastor, I would be telling them about condoms, contraceptives and PrEP" - conflicts, dilemmas and credibility: qualitative insights from religious leaders and the promotion of pre-exposure prophylaxis (PrEP) in Eswatini - Goymann, Hannah; Berner-Rodoreda, Astrid; Mavuso, Mxolisi; McMahon-Rössle, Shannon A.; Matse, Sindy; Jahn, Albrecht; Bärnighausen, Kate (BMJ global health, 2025)
Background Religious leaders (RLs) form an influential group in Eswatini. This study explores their understanding and acceptance of pre-exposure prophylaxis (PrEP), with a view to improve PrEP service delivery for those who would benefit from PrEP the most.Methods We conducted online and in-person in-depth interviews with (n=26) purposefully selected RLs (n=12 female and n=14 male) from Eswatini. Data were managed using NVivo V.12 and coded inductively. We used thematic analysis to analyse our data and structure our findings across the individual, interpersonal, community and institutional levels of an ecological framework.Results RLs have the willingness, potential and influence to promote PrEP in their church communities. They are aware of the community need for HIV prevention, but describe a conflict between their professional role as a pastor and their personal commitment to the well-being of their church community. Participants expressed a dilemma between their pastoral ethics— which oppose sex outside of marriage—and the conflicting challenges of HIV stigma and evidence-based health promotion among church members. Discussing PrEP could compromise their credibility and expose them to potential censure from religious authorities and the church community.Conclusion RLs can play an important role in the community acceptance and implementation of PrEP but are conflicted between community health and their professional role. Addressing the sources of this conflict and offering tailored training about HIV prevention and PrEP is essential to reduce stigma and benefit from RLs’ influence in the church community.
Gesehen am 17.10.2025